PENGABDIAN KKN-MANDIRI TEMATIK KELURAHAN ONEKORE KABUPATEN ENDE - Yulita Londa; Yulita Tanda; Yohanes F Senda; Yanuaris B Gabe; Sirilus Sandy Banda; Kristian E Turu More; Hedwig Hendra Tegu Rani (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The general theme of the 2020 Community Service Program is “Community Empowerment”. Meanwhile, the special theme is "Entrepreneurship". The implementation time starts from August 3 to September 3, 2020, in Onekore Village, Ende Tengah District, Ende Regency. On the program. With this special theme, the main activity carried out is supporting entrepreneurship in Onekore Village. The purpose of implementing this activity is that students are expected to gain learning experience through direct involvement in the community in finding, formulating, solving, and overcoming problems in the field. In this KKN activity, the problems found were the lack of utilization of existing garden products, namely bananas. So far, it is consumed by boiling or eating it without further processing. Olso besides, we also found woven products from weaving that were difficult to market. Students socialize and practice entrepreneurship as an effort to solve problems faced by weaving craftsmen. Efforts made to help the household economy include making flower pots and making wallets made from woven fabrics. Supporting activities during the Community Service Program are assisting with the administration of the Village, community service, building a gate for the Indonesian Independence Day, making sample gardens, socializing COVID-19 and, health service for the elderly.